1980
DOI: 10.1136/vr.106.23.473
|View full text |Cite
|
Sign up to set email alerts
|

Bovine virus diarrhoea-mucosal disease virus: pathogenicity for the fetal calf following maternal infection

Abstract: Fifteen pregnant, bovine virus diarrhoea-mucosal disease (BVD-MD) antibody-free Jersey heifers were infected experimentally with a mixture of 10 cytopathic strains of BVD-MD virus isolated from cattle in Britain. Each cow was inoculated intramuscularly on gestation day 100 with a high or a low dose of virus grown in primary calf testis tissue cultures. None of the cows showed clinical signs of illness following exposure, but all had seroconverted within six weeks. Six fetuses, including one set of twins, died … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
85
2
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(93 citation statements)
references
References 0 publications
3
85
2
1
Order By: Relevance
“…5,9,17 NcpBVDV, by virtue of its ability to cross the placenta and infect the fetus at any stage of gestation, has been associated with a myriad of different manifestations, including early embryonic death, abortion, fetal PI, and congenital abnormalities. 2,10,11 The fetal consequences of transplacental infection appear to be primarily determined by the age of the fetus at the time of infection, although other factors may contribute, such as the pathogenicity of the infecting virus strain and the immune and health status of the dam. 4 Transplacental infection of the fetus by ncpBVDV prior to adaptive immune system development, which occurs during the second and third trimesters of gestation, is thought to enable PI and lifelong viral shedding by the animal due to development of highly virus-specific T-cell tolerance to the infecting strain.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…5,9,17 NcpBVDV, by virtue of its ability to cross the placenta and infect the fetus at any stage of gestation, has been associated with a myriad of different manifestations, including early embryonic death, abortion, fetal PI, and congenital abnormalities. 2,10,11 The fetal consequences of transplacental infection appear to be primarily determined by the age of the fetus at the time of infection, although other factors may contribute, such as the pathogenicity of the infecting virus strain and the immune and health status of the dam. 4 Transplacental infection of the fetus by ncpBVDV prior to adaptive immune system development, which occurs during the second and third trimesters of gestation, is thought to enable PI and lifelong viral shedding by the animal due to development of highly virus-specific T-cell tolerance to the infecting strain.…”
mentioning
confidence: 99%
“…10,26,27,32,38 The morphogenesis of these lesions and the mechanisms responsible for their development are unclear. Reduced bone and calcified cartilage core resorption would be the direct explanation, but contributions of other potential processes, including enhanced bone formation or physeal abnormalities leading to the production of thickened primary spongiosa, have not been investigated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Congenital defects develop in the foetus typically when infected during the mid-gestation stage (Radostits and Littlejohns 1988). CNS defects include cerebellar hypoplasia (Ward et al 1969), microencephalopathy, hydrocephalus and hydranencephaly (Badman et al 1981), while incidences of optic neuritis, alopecia (Yeruham et al 2001) and growth retardation have also been observed (Done et al 1980). …”
Section: Pathogenesismentioning
confidence: 99%
“…Major economic losses due to BVDV infection include reduced fertility, abortions, growth retardation and the generation of persistently viremic calves, which can develop fatal "mucosal disease" (Brownlie, 1990;Bielefeldt, 1995;Moennig and Liess, 1995). Placental infection with ncp virus in the first trimester of gestation can induce persistently viremic calves (Moennig and Liess, 1995), whereas fetal infection later in gestation often causes abortion, retarded development or results in healthy virus-free and seropositive offspring (Done, et al, 1980;Bielefeldt, 1995). Persistently infected lifelong virus carriers play a key role in BVDV epidemiology.…”
Section: Introductionmentioning
confidence: 99%